Study about The Infection-Free Equilibrium Point of a Mathematical Model Dynamics of Transmission HIV/AIDS in a Active Heterosexual Population in Peru with Application to Public Health - López Cruz, Roxana (2016)
We present the analysis of a mathematical model applied to Epidemiology. It explains the dynamics of transmission of the disease of the Acquired Immunodeficiency Syndrome (AIDS) among eterosexually active people using natural and non natural protection. We study the sensitivity of the model with respect to its local stability to the Infection-Free Equilibrium Point and Computational Simulations. This provides an understanding of the dynamic of the model to take decisions in the area of Public Health, taking into account the social and economical aspects.